1999
DOI: 10.1046/j.1440-6055.1999.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Size of the first spring generation of Helicoverpa punctigera (Wallengren) (Lepidoptera: Noctuidae) and winter rain in central Australia

Abstract: Serious infestations of Helicoverpa punctigera are experienced yearly in the eastern cropping regions of Australia. Regression analysis was used to determine whether the size of the first generation in spring (G1), which is comprised mostly of immigrants from inland Australia, was related to monthly rainfall in inland winter breeding areas. Data from two long series of light‐trap catches at Narrabri in New South Wales (NSW) and Turretfield in South Australia (SA) were used in the analyses. The size of G1 at Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 12 publications
(16 reference statements)
2
42
0
2
Order By: Relevance
“…For example, because of a historical absence of entomological expertise in central Australia many of the surveys that have been undertaken there have been (1) Ôsnap shotÕ surveys of short duration targeting species for taxonomic research or for new locality and temporal records (e.g., GrifÞn 1979, Allsopp andLloyd 1987), or (2) longer term surveys of invertebrates whose identiÞcations are at high taxonomic ranks (often at ordinal level or at least reported at ordinal level) to indicate food availability for vertebrates (e.g., Read 1987, GilÞllan 2001. Other, more speciÞc studies in the arid zone have examined the effects of climate on abundance, phenology and migration of pest species such as the Australian plague locust Chortoicetes terminifera (Walker) (e.g., Wright and Symmons 1987), the Australian bushßy Musca vetustissima (Walker) (e.g., Hughes et al 1972), and the native budworm Helicoverpa punctigera (Wallengren) (e.g., Oertel et al 1999). Another study reported the effects of precipitation on butterßy species diversity and migration Australia-wide (Dingle et al 2000).…”
mentioning
confidence: 99%
“…For example, because of a historical absence of entomological expertise in central Australia many of the surveys that have been undertaken there have been (1) Ôsnap shotÕ surveys of short duration targeting species for taxonomic research or for new locality and temporal records (e.g., GrifÞn 1979, Allsopp andLloyd 1987), or (2) longer term surveys of invertebrates whose identiÞcations are at high taxonomic ranks (often at ordinal level or at least reported at ordinal level) to indicate food availability for vertebrates (e.g., Read 1987, GilÞllan 2001. Other, more speciÞc studies in the arid zone have examined the effects of climate on abundance, phenology and migration of pest species such as the Australian plague locust Chortoicetes terminifera (Walker) (e.g., Wright and Symmons 1987), the Australian bushßy Musca vetustissima (Walker) (e.g., Hughes et al 1972), and the native budworm Helicoverpa punctigera (Wallengren) (e.g., Oertel et al 1999). Another study reported the effects of precipitation on butterßy species diversity and migration Australia-wide (Dingle et al 2000).…”
mentioning
confidence: 99%
“…5), evidence for field resistance to insecticides was not recorded in this species until relatively recently (Gunning et al 1997b). This is probably due to the ecology and population structure of H. punctigera which breeds on native host plants in the absence of insecticides in inland Australia (Zalucki et al 1986(Zalucki et al , 1994Gregg et al 1995;Oertel et al 1999). Helicoverpa punctigera re-invades agricultural regions annually (Fitt et al 1989;Maelzer et al 1996;Maelzer & Zalucki 1999Zalucki & Furlong 2005).…”
Section: Area Of Cotton 000 Hamentioning
confidence: 99%
“…In addition, H. punctigera was believed to develop large populations in inland areas, which migrated into cotton regions during late spring where they were thought to be obligate migrants (Oertel et al 1999;Gregg et al 2001). As these moths had originated from non-cultivated habitats and not been exposed to agricultural insecticides, they should be susceptible and hence interbreed with potentially resistant remnant populations of H. punctigera that may have remained in the cotton regions from the previous season, hence diluting any resistance.…”
Section: Supporting the Rmp And Advancing Knowledge Of Helicoverpa Spmentioning
confidence: 99%